Subjective Criticism - Bleich, David (Johns Hopkins University Press, 2019)
Originally published in 1981. The meaning and objectives of literature, argues David Bleich, are created by the reader, who depends on community consensus to validate his or her judgements. Bleich proposes that the study of English be consciously reoriented from a knowledge-finding to a knowledge-making enterprise. This involves a new explanation of language acquisition in childhood, a psychologically disciplined concept of linguistic and literary response, and a recognition of the intellectual authority of pedagogical communities to originate and establish knowledge. Amplifying his theoretical model with subjective responses drawn from his own classroom experience, Bleich suggests ways in which the study of language and literature can become more fully integrated with each person's responsibility for what he or she knows.